Varietal effect on the moisture adsorption isotherm of yellowfleshed cassava root starches - Awoyale, W.; Sanni, Lateef O.; Shittu, T.A.; Adegunwa, M.O.; Gueye, B.; Kulakow, Peter A. (2014)
The Moisture Adsorption Isotherm of three Yellow-fleshed Cassava Root Starches (YfCRS) were determined by the static gravimetric method at temperatures of 27 oC, 37 oC and 42 oC and water activities level of between 0.10 and 0.80. Data obtained were fitted to four sorption models (Peleg, GAB, Oswin and Langmuir). The model fit was evaluated using the coefficient of determination (R2), root mean square error (RMSE) and mean percentage deviation (%E). The results showed that Peleg model gave the best fit for predicting the moisture adsorption data of the starches (R2=0.99, RMSE=0.00, %E=0.00). TMS 06/1630 YfCRS had the highest monolayer moisture (M ) while that of TMS 01/1368 had the lowest. The high B-carotene content of TMS 01/1368 YfCRS could be responsible for its low M (r = -0.96), irrespective of the storage temperatures. However, all the YfCRS might be stored for longer periods at all the temperatures since their M fall within acceptable limit for storage stability.